"Being There": An Empirical Logic Model for Family Presence During Resuscitation and Invasive Procedures. - Halm, Margo A.; Ruppel, Halley; Sexton, Jessica (American Journal of Critical Care, 2025)
Family presence during resuscitation and invasive procedures emerged as a practice innovation in the early 1980s in response to family needs during critical health care situations. By the 1990s, the American Association of Critical-Care Nurses, along with numerous other organizations, had formally supported this intervention and developed practice alerts, position statements, and other evidence-based guidelines. As the practice spread, researchers stepped up to investigate patient, family, and health care team outcomes. Today, family presence is practiced and studied across the globe. This article describes an empirical "Being There" model of the family presence intervention based on more than 125 pieces of external evidence. Using a logic model framework, it outlines the components of a family presence program, including the situation and priorities, inputs, outputs, outcomes/impact, assumptions, and external factors. This model can be used by units and organizations interested in revitalizing or initiating a family presence program in pediatric or adult emergency, high-acuity, or critical care settings. Program development and evaluation suggestions are offered, as well as recommendations for implementation science research to identify the most effective strategies for helping health care teams adopt and sustain family presence programs to meet patient and family needs in vulnerable health care moments.